Analisis Tentang Pengaruh Investasi Terhadap Pertumbuhan Ekonomi dan Penyerapan Tenaga Kerja Provinsi di Pulau Sumatera, Indonesia - Bonaraja Purba (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2020)
This study aims to analyze the effect of investment (PMDN and PMA) on economic growth and employment in eight provinces on the island of Sumatera, Indonesia. The research period is five years, from 2013 to 2017 using secondary data from the Central Bureau of Statistics with a combination of time series and cross sectional data. To estimate the effect of independent variables on the dependent variable the panel data regression equation model is used. The results showed that in the provinces of Sumatera Island: (a) PMDN investment had a positive and significant effect on economic growth, (b) PMA investment had a positive and significant effect on economic growth, (c) PMDN investment had a positive and significant effect on employment, (d) PMA investment has a negative and significant effect on employment.